Development of bio-based nanocomposites from modified corn husk cellulose and green-synthesized nanoparticles - Deniz, Sermin; Kar, Filiz; Karatas, Mukaddes; Erzen, Buket; Aydogmus, Ercan; Orhan, Ramazan (Springer, 2025)
The valorization of agricultural waste for sustainable material development remains an important research focus. This study aimed to develop a bio-based composite with improved functional properties by synthesizing cellulose acetate (CAc) from corn husk and incorporating it into an unsaturated polyester matrix with green-synthesized silver nanoparticles (AgNPs, 0.5 wt.% using rosemary extract). CAc, prepared at different loadings (0.5-5 wt.%), exhibited a degree of substitution (DS) of 2.28 +/- 0.02, as confirmed by alkaline saponification and Fourier transform infrared (FTIR) analysis. The resulting nanocomposites were characterized for their morphological, mechanical, thermal, dielectric, and structural properties. FTIR and XRD analyses confirmed the successful integration of CAc into the polyester matrix, while XRD results indicated that the crystallite size of AgNPs in the nanocomposite was approximately 4.3 nm. Mechanical tests showed that 5 wt.% CAc decreased the tensile strength from 55.3 to 44.7 MPa while increasing the elongation at break from 10.2 to 18.5%, enhancing the ductility. Thermal conductivity decreased from 0.25 to 0.19 W/mK, improving insulation, and the dielectric constant increased from 3.15 to 3.6, indicating enhanced dielectric behavior. These results demonstrate that the polyester/CAc/AgNP nanocomposites offer multifunctional performance for sustainable packaging, structural materials, flexible electronics, and antimicrobial coatings.
Keywords: Corn husk; Cellulose acetate; Green synthesis; Nanoparticles; Polyester; Nanocomposites; Bio-based materials